2019
DOI: 10.1111/nph.16186
|View full text |Cite
|
Sign up to set email alerts
|

Mating system impacts the genetic architecture of adaptation to heterogeneous environments

Abstract: Self-fertilisation has consequences for variation across the genome as it reduces effective population size, effect recombination rates and pollen flow, with implications for local adaptation.We conducted simulations of divergent stabilising selection on a quantitative trait with drift, pollen flow, mutation, recombination and different outcrossing rates. We quantified trait divergence and the genetic architecture of adaptation. We conducted an F ST outlier analysis to identify candidate loci and quantified th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 93 publications
3
40
0
Order By: Relevance
“…A similar conclusion was reached by Olito et al (2018) from a model including male/female antagonism and heterogeneous habitat with full dispersal. Finally, beyond the current work, simulations showed that local adaptation genes tends to aggregate into clusters in outcrossers (Yeaman and Whitlock, 2011) whereas the genetic architecture tends to be more diffuse in selfers (Hodgins andYeaman, 2019, Le Thierry d'Ennequin et al, 1999). Thus, a natural extension of the model would be to consider local adaptation at two loci to dissect the additional effect of selfing on genetic linkage.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…A similar conclusion was reached by Olito et al (2018) from a model including male/female antagonism and heterogeneous habitat with full dispersal. Finally, beyond the current work, simulations showed that local adaptation genes tends to aggregate into clusters in outcrossers (Yeaman and Whitlock, 2011) whereas the genetic architecture tends to be more diffuse in selfers (Hodgins andYeaman, 2019, Le Thierry d'Ennequin et al, 1999). Thus, a natural extension of the model would be to consider local adaptation at two loci to dissect the additional effect of selfing on genetic linkage.…”
Section: Discussionmentioning
confidence: 54%
“…Characterizing the pollination and seed dispersal modes and their quantitative impacts on gene flow appears thus crucial to make proper predictions on the effect of selfing. Finally, if we also consider the effect of linked selection that reduces local effective size beyond the two-fold level in selfing populations (Roze, 2016), selfing reduces the possibility of local adaptation, which requires stronger selection as exemplified by Hodgins and Yeaman (2019) who simulated local adaptation in selfing populations with and without background selection. Overall, the complex and contradictory effects of selfing on local adaptation may explain why no general empirical pattern has emerged so far (Hereford, 2010, Leimu andFischer, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors in this Special Issue develop evolutionary models to explore aspects of plant reproductive systems. Hodgins & Yeaman (, in this issue pp. 1201–1214) employed individual‐based simulations of populations to show that self‐fertilization influences evolutionary divergence of quantitative traits through its effect on limiting gene (pollen) flow, and that evolution of quantitative traits in self‐fertilizing populations may involve a larger number of loci, each with smaller average effects compared to that in outcrossing populations.…”
Section: Evolution Of Plant Reproductive Systemsmentioning
confidence: 99%
“…However, to date, no study has addressed the mechanisms underlying the broad ecological niche of some tree species of tropical forest. Yet, plants experience generations of selection by local environmental conditions due to their limiting gene dispersal through seeds and pollen (Sork, 2016;Grand et al, 2019;Hodgins and Yeaman, 2019). This selection may result in adaptive genetic differentiation (van Kleunen, 2007;Nicolaus and Edelaar, 2018).…”
Section: Introductionmentioning
confidence: 99%